Debate Technique Implementation on Students’ Speaking Skill Acceleration - Pratiwi, Nurjana; Wariyati, Wariyati; Amin, Teguh Satria; Asnawi, Asnawi; Nurlaili (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2024)
Abstract This study aims to analyze the effect of debate techniques on the speaking skills of grade XI students at SMA Al- Washliyah Medan in the 2022/2023 academic year. Speaking skills are an important aspect in involving grade XI students as samples. The results showed that the use of debate techniques significantly improved students' speaking ability. The average pre-test score of the experimental group was 61.32, while the average post-test score increased to 74.73, with English learning, and debate techniques identified as an effective method to improve this ability, especially in vocabulary and pronunciation aspects. This study used a pre-test and post-test experimental design, with an increase of 22%. The t- test results also showed a higher value than the t-table (68.09> 2.023), indicating a significant difference before and after treatment. The conclusion of this study is that the debate technique provides a positive contribution to improving alternative skills in teaching English speaking to create a speaking environment for students. It is recommended that teachers consider using this technique as a more interactive and dynamic learning. Because the debate technique not only improves students' speaking skills, but also motivates them to think critically and be more confident in delivering arguments.